PERAN TEKNOLOGI TERHADAP PERILAKU SOSIAL ANAK: STUDI KASUS PADA SISWA KELAS V SD NEGERI 1 JAYA BAKTI KABUPATEN BUTON SELATAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the intensity and patterns of mobile phone use among fifth-grade students at SD Negeri 1 Jaya Bakti, South Buton Regency, as well as to analyze the role of technology in shaping and transforming students' social behavior, encompassing both its positive and negative impacts on social interaction and the learning process at school. The study employed a qualitative approach using a case study design, which allowed for an in-depth and contextual exploration of phenomena in accordance with the social and geographical characteristics of the South Buton archipelago. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, with validity established through source and technique triangulation. The findings reveal that students use mobile phones an average of two to five hours per day, predominantly engaging with entertainment content such as games and social media, with minimal parental supervision. These conditions have had a tangible impact on the weakening of direct social interaction among students, a decline in collaborative skills, reduced social awareness, and disrupted concentration during classroom learning. On the other hand, a small number of students utilized mobile phones constructively as tools for academic information retrieval, and teacher guidance proved effective in redirecting students' social behavior in a more constructive direction. These findings have direct implications for the achievement of SDG 4 on Quality Education and SDG 10 on Reduced Inequalities, given that children in archipelagic regions are at greater risk of experiencing deeper social developmental disparities without concrete and structured digital policy interventions.